Comprehensive indicators of spending attributes of the middle class: impact on credit card use and retirement savings - Sensenig, Derek Jay (Kansas State University, 2021)
As more organizations forego defined benefit plans, retirement savings adequacy has been a growing concern for workers who want to maintain a balanced lifestyle through their working life and into their retirement years. This dissertation examines the relationship between consumer socialization attributes, credit card usage, and retirement savings using primary data gathered through Amazon Mechanical Turk by means of previously validated scales. The specific consumer socialization outcomes assessed include advertising effectiveness, impulsive buying tendencies, self-control, conspicuous consumption, and consideration of future consequences. The primary focus was to study the mediating effect of credit card usage in the relationship between consumer socialization outcomes and retirement savings. Credit card usage was analyzed through two measures. The first measure consisted of a continuous variable of aggregate credit card balances; the second was a categorical variable with three components – (a) a null user, who is a respondent who does not own a credit card, (b) a convenience user, who is a respondent who does not maintain an ongoing monthly balance on his or her credit cards, and (c) a revolving user, who is a respondent who has maintained a revolving balance on his or her credit cards at least once in the last 12 months. These two measures of credit card spending were important features of this study since an overarching objective was to comprehensively understand the impact of credit card spending for people in the middle-class. Credit card overspending was a key consideration for the study since credit card debt may supersede seemingly less-urgent priorities, like retirement savings. Overspending could occur with both convenience and revolving users because wealth and income are finite, and as such, the money used to maintain a zero-balance credit card could thwart the ability to save for retirement. The specification of middle-class respondents is also an essential element of the study since they are uniquely positioned mathematically, based on income, to save for retirement, but they must strategically monitor all aspects of their spending to actualize the savings for retirement. This research considers how the consumer socialization agents of influence by mass media, peers, and parents (Moschis & Churchill, 1978) relate to and affect retirement savings and the mediating effect of credit card usage. Structural equation modeling (SEM) was used to analyze the relationship between the attributes of the three latent variables (mass media socialization, subjective behavioral socialization, consumer socialization), dependent variable (retirement savings), and mediating variables (credit card usage and credit card balance). Bootstrapping was used to evaluate the mediating effects of credit card usage on the relationship between consumer socialization attributes and retirement savings. Results from this study revealed that there was a statistically significant relationship between the consumer socialization latent variable and retirement savings, as well as consumer socialization and both credit card balances and credit card user type. However, the outcomes of the study demonstrated that neither credit card usage nor credit card balances was a mediating factor for retirement savings. Mediating variables were tested simultaneously and individually resulting in further support for a lack of mediating effect. Furthermore, this research revealed that, in general, participants can both save for retirement and manage credit card spending. The outcomes of this study serve as a starting point for understanding the association between consumer socialization, credit card usage, and retirement savings. This current research provides an exploratory evaluation of the role consumer socialization plays in retirement savings and credit card usage. The findings should be of most interest to financial planners, financial therapists, client psychologists, and behavioral scientists.
Keywords: Credit cards; Retirement savings; Consumer socialization